Uterine cellular leiomyomas are characterized by common HMGA2 aberrations, followed by chromosome 1p deletion and MED12 mutation: morphological, molecular, and immunohistochemical study of 52 cases - Dundr, Pavel; Gregová, Mária; Hojný, Jan; Krkavcová, Eva; Michálková, Romana; Němejcová, Kristýna; Bártů, Michaela; Hájková, Nikola; Laco, Jan; Mára, Michal; Richtárová, Adéla; Zima, Tomáš; et al. (Virchows Archiv, 2022)
Cellular leiomyoma (CL) represents an uncommon variant of uterine leiomyoma with limited data concerning its immunohistochemical and molecular profile. We performed a comprehensive analysis of 52 CL cases all of which were analyzed immunohistochemically. Molecular analysis was possible in 32 cases with sufficient DNA, and 38 cases with sufficient RNA. The immunohistochemical results showed a high expression of smooth muscle markers (calponin (100%), desmin (100%), smooth muscle actin (98.1%), caldesmon (96.1%), transgelin (96.1%), smooth muscle myosin heavy chain (86.5%), and smoothelin (61.5%)). Concerning markers of endometrial stromal differentiation, the expression of CD10 was observed in 65.4% cases (42.2% with H-score > 50), and IFITM1 in 36.5% cases (1.9% with H-score > 50). 36.5% showed HMGA2 overexpression at the IHC level, associated with increased mRNA expression in 14/14 cases. The rearrangement of the HMGA2 gene was detected in 13.2%. Chromosome 1p deletion was found in 19.3%, while 9.4% of tumors showed a pathogenic mutation in the MED12 gene. In conclusion, CL is immunohistochemically characterized by a high expression of "smooth muscle" markers commonly associated with a co-expression of "endometrial stromal" markers, where IFITM1 shows superior performance compared to CD10 regarding its specificity for differentiation from endometrial stromal tumors. The sensitivity of smoothelin in CL seems rather low, but no data is available to assess its specificity. On a molecular level, the most common mutually exclusive aberration in CL affects HMGA2, followed by chromosome 1p deletions and MED12 mutations.
Keywords: nádory endometria; mutace; Female; protein HMGA2; ženské pohlaví; lidé; Uterine Neoplasms; neprilysin; Mutation; nádory dělohy; Neprilysin; Chromosomes; Mediator Complex; Leiomyoma; Endometrial Neoplasms; HMGA2 Protein; mediátorový komplex; leiomyom; chromozomy; Humans